Impact of Fire on the Genetic Variability of a Natural Population of Stylosanthes hippocampoides (Fabaceae) in Corrientes, Argentina - Arcangeli , Julieta Berenice; Lavia, Graciela Inés; Silvestri, María Celeste (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2026)
Stylosanthes hippocampoides, a native legume forage species, was first studied by our research team in 2016 to assess genetic variability in natural populations in northeastern Argentina. Recurrent fires in the following years raised concerns about their effects on population genetics. This study aimed to evaluate and compare the genetic variability and structure of S. hippocampoides populations before and after fire events, and to infer whether such disturbances influence genetic diversity. Using Geographic Information System tools, we selected one fire-affected population (ASI) and one unaffected population (TC). Genetic analyses were conducted using inter-simple sequence repeat markers, and pre- and post-fire genetic statistics were compared. Greater genetic variability was observed between populations than within them. The TC population exhibited higher intra-population genetic diversity than the ASI population. Genetic variability decreased in ASI post-fire, while TC slightly increased. However, neither change was statistically significant. Genetic structure analysis consistently grouped individuals by population, regardless of fire exposure. These findings provide a foundation for future research on Stylosanthes, incorporating additional populations with varied fire histories and examining post-fire recovery processes. Highlights: Fire impact on genetic variability of Stylosanthes hippocampoides populations in Corrientes Argentina were assessed. This is a preliminary study supporting fire-related conservation planning efforts. Genetic variability was higher among than within populations. Post-fire population showed genetic decline, not statistically significant. Genetic structure grouped individuals by population in all comparisons. This study explores fire effects and recovery in Stylosanthes.